Game RPG Berbasis Jamur Pangan - Lauw Hermawan Pratama Lauwoto; Alexander Setiawan; Justinus Andjarwirawan (Jurnal Infra, 2020)
With the development of open-source technology such as Android, it helps new learning media, namely games. Games can be used to introduce something that rarely know such like edible mushrooms. Therefore, so it’s expected that this game can introduce edible  mushrooms.The game application that will be made in the RPG genre runs on the Android operating system with the Java programming language. With the main theme based on edible mushroom,  which all characters in the game are related to edible mushrooms from characters to NPC enemiesThe results of the development of this game show that the game is not only an entertainment media but also can be a medium of learning to get to know something new.